Modeling of Fuzzy Z-Number Control System Based on Interpolation Approach Mechanism - Mammadova, K.A.; Alieva, A.A. (Herald of Azerbaijan Engineering Academy, 2025)
In most cases, in the modeling of fuzzy control systems, the reliability of the linguistic values of the variables in the rule base is of great importance. It is important to design the inference mechanism taking into account the reliability of the fuzzy values of the variables of the rules. For this purpose, fuzzy rules based on the Z number, which include the restrictions and reliability of information, are constructed. The interpolation of fuzzy rules is presented for the design of the inference engine of a system based on fuzzy rules. A mathematical model of a fuzzy inference system based on an interpolative mechanism is developed. A fuzzy control system with the Z number for controlling a dynamic object is modeled based on the interpolative inference mechanism. The transition process of the designed controller is compared with the transition process of a conventional fuzzy controller. The obtained comparative results demonstrate the suitability of the modeled systems in controlling dynamic objects.